Impact of trade openness on GDP growth: Does TFP matter?. Issue 8 (17th November 2019) - Ramzan, Muhammad; Sheng, Bin; Shahbaz, Muhammad; Song, Jian; Jiao, Zhilun
ABSTRACT: The objective of this study is to empirically explore the impact of trade openness on GDP growth initiating with the idea that trade openness cannot be fully characterized through the different openness measures only, we propose to account for total factor productivity (TFP) development level as an additional dimension of countries' trade integration. Our empirical application is based on 35 years' balanced panel of 82 countries spanning 1980–2014. To address the potential endogeneity issue, we use the system GMM estimator developed for dynamic panel data models. The results outline that there exists an interesting non-linear pattern between trade openness and GDP growth when TFP development level is taken as an intervening variable into account: trade may have a negative impact on GDP growth when countries have specialized in low-TFP development level; trade openness clearly boosts GDP growth once countries exhibit a minimum threshold of TFP development level. Therefore, there is some pattern of complementarity between trade openness and TFP development level so that the higher the TFP development level, the higher the impact of the trade openness on GDP growth.